Monocarboxyoctyl phthalate is associated with platelet count: evidence from a large cross-sectional study - Zhang, Jian; Xie, Yuhan; Chen, Jinqiu; Song, Lei (Frontiers in Public Health, 2025)
IntroductionPhthalates are environmental pollutants that are harmful to human health. However, the impact of phthalate on platelet count remains unclear. This study aimed to examine the correlation between five phthalate metabolites in urine and platelet count, as well as the impact of phthalate metabolite exposure on platelet count in adults.MethodsThis cross-sectional study included 11,409 non-pregnant participants aged >20 years using data available from the National Health and Nutrition Examination Survey (NHANES) between 2005 and 2018. Weighted logistic regression, restricted cubic spline (RCS) modeling, and weighted quantile sum (WQS) were employed to investigate the effects of mono-(carboxyisononyl) phthalate (MCNP), mono-(carboxyoctyl) phthalate (MCOP), mono-(3-carboxypropyl) phthalate (MCPP), mono-isobutyl phthalate (MiBP) and mono-isononyl phthalate (MNP) on platelet count.ResultsLogistic regression analysis suggested that MCOP [odds ratio (OR) (95% confidence interval CI) = 0.009 (0.002–0.036)] was significantly associated with the platelet count. Subgroup analysis showed negative correlations between MCOP and platelet count across all age and sex groups, and MCNP [OR (95% CI) = 0.083(0.013–0.552)] displayed a negative association with platelet count in females. MCOP had a nonlinear relationship with the platelet count in the RCS model. WQS also revealed that MCOP was related to platelet count.ConclusionHigher urinary MCOP level was associated with lower platelet count. Further investigation is necessary to substantiate these findings, considering the shortcomings of the NHANES study.